2020
DOI: 10.1101/2020.02.21.958231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep Deprivation alters the influence of biological sex on active-phase sleep behavior

Abstract: Poor sleep is a hazard of daily life that oftentimes cannot be avoided. Gender differences in daily sleep and wake patterns are widely reported; however, it remains unclear how biological sex, which is comprised of genetic and endocrine components, directly influences sleep regulatory processes. In the majority of model systems studied thus far, sex differences in daily sleep amount are predominant during the active (wake) phase of the sleep-wake cycle. The pervasiveness of sex differences in sleep amount thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Males with XX or XY chromosomes spent more time in NREMS than XX or XY females, confirming that gonadal phenotype/hormones regulate NREMS ( Ehlen et al, 2013 ; Nichols et al, 2020 ). However, although GDX greatly reduced this difference in the first study ( Ehlen et al, 2013 ), the difference persists in the latter ( Nichols et al, 2020 ). Therefore, these results seem to indicate that male rodents have more NREMS than females, and that this sex difference is influenced by circulating gonadal hormones and Sry expression, and not by sex chromosomes.…”
Section: Wake/sleep Architecturementioning
confidence: 58%
See 4 more Smart Citations
“…Males with XX or XY chromosomes spent more time in NREMS than XX or XY females, confirming that gonadal phenotype/hormones regulate NREMS ( Ehlen et al, 2013 ; Nichols et al, 2020 ). However, although GDX greatly reduced this difference in the first study ( Ehlen et al, 2013 ), the difference persists in the latter ( Nichols et al, 2020 ). Therefore, these results seem to indicate that male rodents have more NREMS than females, and that this sex difference is influenced by circulating gonadal hormones and Sry expression, and not by sex chromosomes.…”
Section: Wake/sleep Architecturementioning
confidence: 58%
“…An absence of sex difference in time spent in NREMS in mice was reported by one study using a piezoelectric assessment of sleep (no EEG quantification; Wang et al, 2020 ), two studies underpowered to assess sex differences (e.g., n = 3 males) ( Brankack et al, 2010 ; Hellman et al, 2010 ), and two other studies not designed to primarily investigate sex differences ( Grønli et al, 2016 ; Huitron-Resendiz et al, 2018 ). In contrast, we found seven studies having shown that male mice and rats spend more time in NREMS than females ( Ehlen et al, 2013 ; Franken et al, 2006 ; Koehl et al, 2006 ; Nichols et al, 2020 ; Paul et al, 2006 ; Saré et al, 2020 ; Swift et al, 2020 ). In particular, compared to females, C57BL/6 male mice spend more time in NREMS during the dark period, which also brings their daily percentage of NREMS to a greater level ( Paul et al, 2006 ).…”
Section: Wake/sleep Architecturementioning
confidence: 70%
See 3 more Smart Citations